2004
DOI: 10.2460/javma.2004.224.1634
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ceftiofur hydrochloride sterile suspension administered parenterally for the treatment of acute postpartum metritis in dairy cows

Abstract: Ceftiofur hydrochloride administered at a dosage of 2.2 mg of CE/kg, SC or IM, once daily for 5 days was efficacious for treatment of APM in dairy cows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
149
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(161 citation statements)
references
References 9 publications
9
149
1
2
Order By: Relevance
“…At present systemic treatment using ceftiofur is preferable for the treatment of puerperal metritis (Drillich et al, 2001(Drillich et al, , 2003Zhou et al, 2001;Risco and Hernandez, 2003;Chenault et al, 2004). Nevertheless, comparable cure rates and reproductive performances were found in cows with puerperal metritis treated with ceftiofur compared to affected cows treated by the intrauterine administration of ampicillin or ampicillin with oxacillin (Beetz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…At present systemic treatment using ceftiofur is preferable for the treatment of puerperal metritis (Drillich et al, 2001(Drillich et al, , 2003Zhou et al, 2001;Risco and Hernandez, 2003;Chenault et al, 2004). Nevertheless, comparable cure rates and reproductive performances were found in cows with puerperal metritis treated with ceftiofur compared to affected cows treated by the intrauterine administration of ampicillin or ampicillin with oxacillin (Beetz, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown conflicting results on the efficacy of a single dose of long-acting ceftiofur (crystalline fee acid) to reduce the incidence of metritis in cows with risk factors at calving McLaughlin et al, 2013). There are data to support treatment of cows with metritis with ceftiofur or penicillin (LeBlanc, 2008;McLaughlin et al, 2012), but clinical cure is only around 75% to 80% over 10 to 14 days as compared with 62% in untreated cases (Chenault et al, 2004). The impacts of treatment for metritis on subsequent health and reproductive performance are unclear and studies with longer follow-up are needed.…”
Section: Metritismentioning
confidence: 99%
“…Concentrations of drug are not maintained consistently above the target levels in the uterus in cows with metritis (von Krueger et al, 2013). Spontaneous clinical resolution occurs in some cases (Chenault et al, 2004;McLaughlin et al, 2012) and preliminary data suggest that delay of a few days in the onset of treatment of metritis -a 'wait-and-see' approach to allow for spontaneous resolution in perhaps 20% of cases -is worth testing in larger randomized clinical trials.…”
Section: Metritismentioning
confidence: 99%
“…But limits of increased temperatures which are useful for diagnosis of puerperal metritis are not unified. Temperatures of 39.2°C (Smith et al, 1998), 39.5°C (Drillich et al, 2001;Chenault et al, 2004) or 39.7°C (Overton et al, 2003) were described. Because a body temperature of 39.0°C is generally considered to be the maximum value for a physiological condition in cows, temperatures above this value were considered as pathological in our trial.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, measurement of body temperature has been considered a useful method in systemic diagnosis of metritis in early postpartum cows as the disease is often accompanied by fever (Kristula et al, 2001;Zhou et al, 2001;Overton et al, 2003;Benzaquen et al, 2004;Chenault et al, 2004). In spite of introducing body temperature measurement to the monitoring system in dairy herds, there is lack of data proving the contribution of temperature measurement to the diagnosis of puerperal metritis.…”
mentioning
confidence: 99%